A Simpler Method for Predicting Weight Loss in the First Year after Roux-en-Y Gastric Bypass. (19th January 2012) - Sczepaniak Sczepaniak, John P. John P.; Owens Owens, Milton L. Milton L.; Garner Garner, William William; Dako Dako, Farouk Farouk; Masukawa Masukawa, Kristin Kristin; Wilson Wilson, Samuel E. Samuel E.
Abstract : Factors postulated to predict weight loss after gastric bypass surgery, include race, age, gender, technique, height, and initial weight. This paper contained 1551 gastric bypass patients (85.9% female). Operations were performed by one surgeon (MLO) at community hospitals in Southern California from 1989 to 2008 with 314 being laparoscopic and 1237 open. We created the following equation: In[percent weight] = A t 2 - B t, where t was the time after operation (days) and A and B are constants. Analysis was completed on R-software. The model fits with R 2 value 0.93 and gives patients a realistic mean target weight with a confidence interval of 95% for the first year. Conclusion . We created a curve predicting weight loss after surgery as a percentage of initial weight. Initial weight was the single most important predictor of weight loss after surgery. Other recorded variables accounted for less than 1% of variability. Unknown factors account for the remaining 6-7%.